HUBUNGAN KEIKUTSERTAAN ORGANISASI DENGAN REGULASI DIRI PADA REMAJA : STUDI KASUS DI SMA N 2 NGAWI - Rhea Auliya Anggareni; Fitri Hartanto (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2016)
Background : Adolescent is development process from children to adult. Self regulation is one of component adolescent development. The school environment is one of the factors that influence self regulation, in this environment student can follow the activities of the organization.Aim : The aim of this study was to determine the relationship between the organization's participation and self regulation in adolescents.Methods : The method of this study was an observational research with cross sectional approach, began from March to July 2015. Subjects were the students in SMA N 2 Ngawi. SRQ (Self Regulation Questionnaire) and the organization's questionnaire validating before were used to collect data. Data was analyzed by Chi-square testResults : The number of respondents were 80 students, consist of 46 respondent who actively participated in the organization and 34 respondents who are not actively participated in the organization. Students who actively participated in the organization of 21.7% has a good self regulation, 65.3% intermediate and 13% low, while students who do not actively participated in the organization of 8.8% has a good self regulation, 53% intermediate and 38.2% low. The value of probability the relationship between the participation of organizations and self regulation was 0,021 (p <0.05).Conclusion : There is a significant correlation between an organization's participation in self-regulation.